Qualitative analysis of genomic mutations and antibiotic susceptibility testing of Pseudomonas aeruginosa isolates from chronic lung infections - Ad C. Fluit; Jumamurat R. Bayjanov; María Díez Aguilar; Rafael Cantón; Deidre F. Gilpin; Michael M. Tunney; Miquel B. Ekkelenkamp (PLoS ONE, 2026)
P. aeruginosa is intrinsically resistant to many antibiotics and may acquire resistance to others. The aim was to reconcile phenotypic resistance of isolates obtained from patients with chronic respiratory infection with the results of WGS. A total of 497 isolates were recovered from 4 countries between 2002 and 2016 from patients chronic pulmonary conditions, especially cystic fibrosis. Minimum inhibitory concentrations were determined previously by broth microdilution method. Sequencing was performed with Illumina technology and data were analyzed using ResFinder, PubMLST, and the CARD database. In this collection, resistance varied from 4.0% for colistin to 58.8% for ciprofloxacin. Acquired antibiotic resistance genes were found in 17.1% of the isolates, involving six different genes, but could not explain the majority of resistance. Single amino acid changes often did not lead to Minimal Inhibitory Concentrations (MICs) above the EUCAST susceptibility breakpoint. Determining the contribution of each amino acid change to clinical resistance was complicated by the large number of described changes found, the often low frequency of these changes and the high variability of the proteins involved. In particular, the diversity among OXA-ß-lactamases was large; despite over 900 OXA-types in the database, more than half of the variants in the isolate set were undescribed. Resistant isolates frequently had two or more amino acid changes. Four amino acid changes possibly related to β-lactam resistance were more common: two in AmpC (V239A and V356I) and two in PBP3 (R153S and R504C), three of which occurred more often in resistant isolates. Ciprofloxacin resistance could be linked to alterations in GyrA (in particular T82I and D87N) and to loss of or changes in MexZ. AmpD, NfxB, and PmrA, which are associated with resistance, were not detected in similar percentages of resistant and susceptible isolate. It can be concluded that frequently multiple mechanisms make a partial contribution to antibiotic resistance in this set of isolates.